2014
DOI: 10.1186/1744-9081-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in response to apnea impact the timing of motor representations: a preliminary study

Abstract: BackgroundReduced physiological arousal in response to breath-holding affects internal clock processes, leading swimmers to underestimate the time spent under apnea. We investigated whether reduced physiological arousal during static apnea was likely to affect the temporal organization of motor imagery (MI).MethodsFourteen inter-regional to national breath-holding athletes mentally and physically performed two 15 m swimming tasks of identical durations. They performed the two sequences in a counterbalanced ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In contrast to the usual physical training in the purposeful sporting activity, the task of training athletes to achieve their ultimate motor, psychological and functional results is solved [13,17]. Therefore, in the process of training and competition athletes feel the burden on the body as a whole and on its separate systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the usual physical training in the purposeful sporting activity, the task of training athletes to achieve their ultimate motor, psychological and functional results is solved [13,17]. Therefore, in the process of training and competition athletes feel the burden on the body as a whole and on its separate systems.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is probably not due to the apnea itself. Previous studies have shown that subjective estimates of time (in the range of seconds) may be affected by changes in heart rate (Meissner & Wittmann, ), including a reduction in heart rate during breath holding (Di Rienzo, Hoyek, Collet, & Guillot, ; Jamin et al, ). However, we measured changes in time estimation after participants had already resumed breathing, when heart rate is known to return rapidly to baseline levels (Andersson & Schagatay, ).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of the optimal functional state of the cardiovascular system in athletes is determined by the short-term tasks of preparation for a specific sport event, as well as its long-term status, which ensures high achievements of sports for a long period of time. The leading limiting chain in the degree of physical fitness of an athlete is the state of the cardiovascular system [6,7,8]. The functional state of the central hemodynamics enables the most rapid detection of signs of overwork and overtraining.…”
Section: Introductionmentioning
confidence: 99%